States of terrorism : a study on the geographic distribution of Islamist terrorism in India - Chawla, Hithalli (Nanyang Technological University, 2021)
This paper looks at the correlation between Islamist terrorism and the composition of the elected Legislative Assemblies in India. Using a time series, logit regression analysis in 15 States from 2000-2018 followed by a deductive case study analysis, the paper finds that the composition of State Legislative Assemblies does not usually have a statistically significant correlation with Islamist terrorist attacks. The paper also concludes that externalization of the threat of Islamist terrorism undermines the major role that domestic grievances play in contributing to homegrown terrorist organizations that were found to be responsible for a majority of the attacks in India.